2020
DOI: 10.3390/molecules25112541
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 Activation by Equisetum arvense L. (Horsetail) Modulates Insulin Sensitivity in Streptozotocin Induced Diabetic Rats

Abstract: BACKGROUND: Equisetum arvense L., commonly known as field horsetail is a perennial fern of which extracts are rich sources of phenolic compounds, flavonoids, and phenolic acids. Activation of SIRT1 that was shown to be involved in well-known signal pathways of diabetic cardiomyopathy has a protective effect against oxidative stress, inflammatory processes, and apoptosis that are the basis of diseases such as obesity, diabetes mellitus, or cardiovascular diseases. The aim of our study was to evaluate the antidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…An important role in the defense of the organism against infection has lymphoid tissue associated in the intestinal immunity, which is called innate immunity [ 19 ]. Regarding the oxidative stress in metabolic syndrome and diabetes, we can also intervene with the help of plants [ 20 ]. In 2016, Andersen et al highlighted the effect of obesity on the immune response to pathogens, as well as a disruption of the function of associated lymphoid tissue due to fat tissue [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…An important role in the defense of the organism against infection has lymphoid tissue associated in the intestinal immunity, which is called innate immunity [ 19 ]. Regarding the oxidative stress in metabolic syndrome and diabetes, we can also intervene with the help of plants [ 20 ]. In 2016, Andersen et al highlighted the effect of obesity on the immune response to pathogens, as well as a disruption of the function of associated lymphoid tissue due to fat tissue [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely used in Europe, mainly due to its two diuretic properties. Although many studies confirm the potential of these species in the treatment of diabetes in animal models and in vitro studies, there are few clinical studies confirming their hypoglycemic effect (Sidana et al, 2017;Mariángel, 2019;Hegedűs et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In other work, it was proved that horsetail extract is recommended for patients suffering from diabetes because it promotes the regulation of blood glucose levels and the regulation of insulin resistance. Moreover, it was reported that this extract shows potential in the prevention of cardiomyopathy [29].…”
Section: Introductionmentioning
confidence: 99%